Effects of transgenerational photoperiod experience on the reproduction and development of Anastatus orientalis, an egg parasitoid of the spotted lanternfly - Bao, Ke-xin; Wang, Xiao-yi; Cao, Liang-ming; Xin, Bei; Broadley, Hannah J.; Gould, Juli R. (Frontiers in Insect Science, 2023)
Transgenerational experience can affect a wide range of natural enemies’ life-history traits and can be involved in the control of developmental plasticity. As a major egg parasitoid of the spotted lanternfly, Lycorma delicatula (Hemiptera: Fulgoridae), the wasp Anastatus orientalis (Hymenoptera: Eupelmidae) is very effective at suppressing its host populations. The reproductive and developmental traits of A. orientalis is known to depend on photoperiod conditions. Direct photoperiodic effects on reproductive and developmental traits of A. orientalis have previously been investigated, but transgenerational photoperiodic effects have yet to be evaluated. To evaluate the transgenerational photoperiodic effects on A. orientalis, we assessed the wasp’s adult longevity, female fecundity, sex ratio, and diapause rate over three consecutive generations under different experimental photoperiods (L16:D8, L12:D12, and L8:D16), using Antheraea pernyi (Lepidoptera: Saturniidae) eggs as hosts. The results suggest that transgenerational experience significantly impacts several biological parameters of progeny. All parasitoids entered a diapause under the long photoperiod condition (i.e., L16:D8), after which the number of female parasitoids and fecundity of the 2nd and 3rd generations increased significantly as compared to the 1st generation. With the long photoperiod conditions, the female ratio rose from 68.1% (1st generation) to 86.0% (3rd generation) and the progeny per females produced increased from 35.8 to 75.7. However, adult longevity of female and male were shortened significantly as compared to the other conditions. With the intermediate photoperiod (L12:D12) conditions, fecundity and sex ratio of the 2nd and 3rd generations increased significantly as compared to the 1st generation. With the short photoperiod (L8:D16) conditions, there were no significant differences in fecundity among three generations, but sex ratio of the 2nd and 3rd generations increased significantly as compared to the 1st generation. These results can be applied to improve laboratory rearing efficiency of parasitoids and to better understand population dynamics in the field across a latitudinal gradient.